2021
DOI: 10.1016/j.asmr.2021.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Endoscopic Gluteus Medius Repair Can Achieve Successful Clinical Outcomes at Minimum 2-Year Follow-up

Abstract: Purpose: To report on clinical presentations and outcomes in patients who underwent an isolated endoscopic gluteus medius (GM) repair. Methods: We retrospectively reviewed and prospectively collected data on patients who underwent a primary isolated endoscopic GM repair. Patients were included if the following patient-reported outcome scores were obtained preoperatively and at minimum 2-year follow-up: modified Harris Hip Score (mHHS), Non-arthritic Hip Score (NAHS), and visual analog scale (VAS) score. The mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
(28 reference statements)
1
6
0
Order By: Relevance
“…The patients who did not require conversion to THA had a significant preoperative to postoperative improvement in all PROs (P < .01 for all) (Table 5). Additionally, these patients reported high satisfaction (defined as 7/10) 25 at the minimum 2-and 5-year time points (7.2 ± 2.7 and 7.1 ± 2.4, respectively). Also, 16 patients (94.1%) achieved the MCID for the NAHS, and 13 patients (92.9%) achieved the MCID for the HOS-SSS (Table 6).…”
Section: Surgical Outcomesmentioning
confidence: 89%
“…The patients who did not require conversion to THA had a significant preoperative to postoperative improvement in all PROs (P < .01 for all) (Table 5). Additionally, these patients reported high satisfaction (defined as 7/10) 25 at the minimum 2-and 5-year time points (7.2 ± 2.7 and 7.1 ± 2.4, respectively). Also, 16 patients (94.1%) achieved the MCID for the NAHS, and 13 patients (92.9%) achieved the MCID for the HOS-SSS (Table 6).…”
Section: Surgical Outcomesmentioning
confidence: 89%
“…Other studies also demonstrated improved visual analogue scale scores from 8 to 2 and from 6 to 4. 8 , 9 Although these improvements are promising, a 2-year follow-up study demonstrated that only 68% of patients returned to preoperative activity, with 23% of patients unable to return directly related to issues with the operative hip. 10 Kirby et al.…”
Section: Discussionmentioning
confidence: 99%
“…The anchors are then placed, followed by confirmation with fluoroscopy. The tears of the gluteus medius of the lateral facet are generally repaired with four anchors spaced evenly across the tendon footprint [ 17 ]. A penetrator is used to pass the suture through the tendon edge.…”
Section: Methodsmentioning
confidence: 99%